A tale of two eddies: The biophysical characteristics of two contrasting cyclonic eddies in the East Australian Current System. Issue 3 (28th March 2017) - Roughan, M.; Keating, S. R.; Schaeffer, A.; Cetina Heredia, P.; Rocha, C.; Griffin, D.; Robertson, R.; Suthers, I. M.
Abstract: Mesoscale cyclonic eddies are known to be highly productive. Less well‐known are the dynamics and productivity of smaller cyclonic eddies, known as frontal eddies, that form on the landward side of western boundary currents. In this study, we investigate the physical and biogeochemical properties of two contrasting cyclonic eddies in the East Australian Current (EAC). The first ("Murphy"), a mesoscale cyclonic eddy that formed at ∼28°S with a diameter of ∼160 km and high surface chlorophyll‐a concentrations, which lived ∼47 days. The second ("Freddy"), a smaller frontal eddy (∼35 km diameter) that formed from a shelf water billow ∼7 days prior to sampling at ∼31.5°S and was advected off the shelf along the EAC front (from ∼200 m to 4000 m of water). Both eddies were at least 1000 m deep with a similar steric height anomaly. We introduce and employ "the method of closest approach" using shipboard ADCP velocities to estimate the eddy centers, which reveals significant tilting through the water column. We estimate rotation rates of 4–10 days and 1–9 days and Rossby numbers 0.25–0.1 and 0.6–0.1, from the surface to 600 m for Murphy and Freddy, respectively. High‐resolution altimetry measurements from the SARAL/AltiKA satellite provide estimates of the ageostrophic component of rotation. Our results show that the frontal eddy is significantly more ageostrophic, energetic, and productive than the mesoscale cyclone, despite its small size and short life (∼4 weeks). We suggest that frontal eddies have potential to contribute significantly to the net productivity of the Tasman Sea region. Plain Language Summary: We present the first depth observations of a small cold core eddy which formed along the landward front of the East Australian Current. We contrast the observations with a typical larger cold core eddy. The observations were collected from a dedicated cruise aboard a research vessel. We show that this small Frontal Eddy is very dynamic feature. It rotates rapidly, extends to more than 1000 m in depth and is highly productive. We believe these features make a significant contribution to the productivity of western boundary current regions. Key Points: We contrast a suite of 3‐D observations of a cyclonic frontal eddy (∼35 km), and a mesoscale cyclonic eddy (∼160 km) in the Tasman Sea The frontal eddy was short lived (∼ 4 weeks), deep (∼1000 m), highly ageostrophic, and dynamic. Both eddies were tilting Both eddies were productive, however the productivity of the frontal eddy which formed on the shelf was proportionately higher